Mechanical Characterization of the Flax/Epoxy Composite Material. (2015) - Cerbu, Camelia
Abstract: The paper focuses on the mechanical characterization of the composite material made of epoxy resin reinforced with flax fabric. The mechanical behavior of flax / epoxy composite material was analyzed by using tensile test, flexural (bending) test and impact test (Charpy method). After the statistical processing of the experimental data recorded for all specimens tested, the average values of the following properties are determinate: Young's modulus E in tension, tensile normal stress at failure, tensile normal strain at failure, Young's modulus in bending, flexural normal stress at failure, strain energy in all tests (tension, bending, Charpy), resilience recorded in Charpy test. Finally, it reports the average values of the mechanical properties of the flax / epoxy composite material tested. The results show that the average values of the mechanical characteristics recorded on the weft direction of the flax fabric are greater than the ones recorded on the warp direction.